A Retrospective Study on the Influence of Participation at a Student-Run Free Clinic on Medical Specialty Choice - Tang, Cynthia; Win, George; Unangst, Samantha; Haynes, Tricia; Pendergraft, Brittany; Weisenberger, Kaystin; Ohler, Adrienne; Long, Natalie; Young-Walker, Laine (Journal of Student-Run Clinics, 2022)
Background: The MedZou Community Health Clinic at the University of Missouri School of Medicine is a student-run free clinic (SRFC) providing primary care and specialty services to uninsured patients of Missouri. Little is published about the relationship of volunteerism in SRFCs and residency match results. This study evaluated the association of SRFC volunteering on residency placement. We hy-pothesized that there would be an increased likelihood of medical students matching into specialties correlating with specialty clinics they volunteered with as students. Methods: We analyzed data on volunteers who graduated from the University of Missouri School of Medicine between 2010-2019 in this retrospective study. Selection criteria included students who per-mitted publishing their residency match results publicly and actively volunteered for MedZou (at least five volunteer shifts). Odds ratios (OR) were calculated with Fisher exact tests using a confidence in-terval (CI) of 95% to assess whether volunteering in a specialty clinic was associated with matching in that specialty. Clinics with at least five volunteers during the study period were analyzed (Dermatol-ogy, Musculoskeletal [MSK], and Neurology). Results: Twenty-nine percent of the MedZou volunteers that fit the inclusion criteria volunteered for the Dermatology, MSK, or Neurology Clinic. We found significant associations between those who volunteered in a specialty clinic and those who matched in a related specialty for Dermatology (OR = 4.25, 95% CI = 1.37, 12.13), Musculoskeletal (OR = 3.49, 95% CI = 1.45, 7.98), and Neurology Clinics (OR = 10.89, CI = 1.71, 50.39). Additionally, 51% of MedZou volunteers that fit inclusion criteria volunteered for Primary Care Clinic. These students were also found to have a significant association with matching into a related primary care specialty (OR= 2.01, CI= 1.14, 3.62). Conclusions: The results of this study indicated that clinical exposure at a SRFC specialty clinic was associated with residency match into related specialties.